Acinetobacter baumannii Increases Tolerance to Antibiotics in Response to Monovalent Cations - Hood, M. Indriati (American Society for Microbiology (ASM), 2010)
Acinetobacter baumannii is well adapted to the hospital environment, where infections caused by this organism are associated with significant morbidity and mortality. Genetic determinants of antimicrobial resistance have been described extensively, yet the mechanisms by which A. baumannii regulates antibiotic resistance have not been defined. We sought to identify signals encountered within the hospital setting or human host that alter the resistance phenotype of A. baumannii. In this regard, we have identified NaCl as being an important signal that induces significant tolerance to aminoglycosides, carbapenems, quinolones, and colistin upon the culturing of A. baumannii cells in physiological NaCl concentrations. Proteomic analyses of A. baumannii culture supernatants revealed the release of outer membrane proteins in high NaCl, including two porins (CarO and a 33- to 36-kDa protein) whose loss or inactivation is associated with antibiotic resistance. To determine if NaCl affected expression at the transcriptional level, the transcriptional response to NaCl was determined by microarray analyses. These analyses highlighted 18 genes encoding putative efflux transporters that are significantly upregulated in response to NaCl. Consistent with this, the effect of NaCl on the tolerance to levofloxacin and amikacin was significantly reduced upon the treatment of A. baumannii with an efflux pump inhibitor. The effect of physiological concentrations of NaCl on colistin resistance was conserved in a panel of multidrug-resistant isolates of A. baumannii, underscoring the clinical significance of these observations. Taken together, these data demonstrate that A. baumannii sets in motion a global regulatory cascade in response to physiological NaCl concentrations, resulting in broad-spectrum tolerance to antibiotics.